Analysis on Unfair Use of Papers in Education Sector and Preventive Measures to Save Paper - R., Usha Nandhini (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate the paper consumption level, unfair use of papers, attitudes towards the impact of paper wastage,, and suggested preventive measures for sustainable development among the undergraduate and postgraduate students (N=50) from various courses at Dr. M.G.R. Educational and Research Institute, Chennai. Data were collected through a questionnaire to which all the students provided their responses. This analysis helped in collecting the information, and conclusions were drawn, and it's validated through the SPSS software. In common, 90% of students reported that they like to read digitalized materials to avoid the burden of carrying or misplacing them. Students were tuned in to paper reusing, sustainable development, and the impact of paper wastage on the environment, such as deforestation, climate change, pollution, etc. Hence, they agreed that using paper in an efficient manner will support achieving sustainability. They also understand that they're liable for the environment that they live in. Significantly, they were influenced by the teacher’s mode in delivering lectures digitally, which made them develop the habit of reading and sharing the course material digitally.